Neutrophil pyroptosis regulates corneal wound healing and post‐injury neovascularisation - Peng Chen; Zhentao Zhang; Lilian Sakai; Yanping Xu; Shanzhi Wang; Kyung Eun Lee; Bingchuan Geng; Jongsoo Kim; Bao Zhao; Qiang Wang; Haitao Wen; Heather L. Chandler; et al. (Clinical and Translational Medicine)
Abstract Rationale The cornea is a unique structure that maintains its clarity by remaining avascular. Corneal injuries can lead to neovascularisation (CNV) and fibrosis and are the third most common cause of blindness worldwide. Objective Corneal injuries induce an immune cell infiltration to initiate reparative processes. However, inflammation caused by sustained immune cell infiltration is known to be detrimental and can delay the healing process. This study was designed to understand the potential role of neutrophil and epithelial cell crosstalk in post‐injury CNV. Methods and results Western blotting and immunostaining assays demonstrated that neutrophils infiltrated corneas and underwent pyroptosis following acute alkali injury. In vivo studies showed that genetic ablation of Gasdermin D (GsdmD), a key effector of pyroptosis, enhanced corneal re‐epithelialisation and suppressed post‐injury CNV. In vitro co‐culture experiments revealed that interleukin‐1β (IL‐1β) was released from pyroptotic neutrophils which suppressed migration of murine corneal epithelial cells. Real‐time RT‐PCR and immunostaining assays identified two factors, Wnt5a and soluble fms‐like tyrosine kinase‐1 (sflt‐1), highly expressed in newly healed epithelial cells. sflt‐1 is known to promote corneal avascularity. Bone marrow transplantation, antibody mediated neutrophil depletion, and pharmacological inhibition of pyroptosis promoted corneal wound healing and inhibited CNV in an in vivo murine corneal injury model. Conclusion Taken together, our study reveals the importance of neutrophil/epithelium crosstalk and neutrophil pyroptosis in response to corneal injuries. Inhibition of neutrophil pyroptosis may serve as a potential treatment to promote corneal healing without CNV. Key points Neutrophil pyroptosis delays re‐epithelialization after corneal injury Compromised re‐epithelialization promotes corneal neovascularization after injury Inhibition of post‐injury pyroptosis could be an effective therapy to promote corneal wound healing.